IMPLEMENTASI KEBIJAKAN UJI KOMPETENSI GURU (UKG) DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA PALEMBANG - Nurbaiti Nurbaiti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study was to determine the implementation of the Teacher Competency Test (UKG) policy at Palembang State High School 10. This study uses descriptive qualitative analysis techniques, with qualitative or naturalistic methods. Data collection uses observation, interview and documentation techniques. Determination of informants is done by snowball sampling. In this sampling technique the researcher had previously determined a key informant as the initial data source. The informants were the Head of Palembang State High School 10, Deputy Head of SMAN 10 Palembang, and 3 teachers from Palembang State High School who participated in the UKG. Data analysis techniques in this study used an interactive analysis method with three stages of qualitative analysis, namely: Data Reduction, Data Presentation, and Conclusion Withdrawal and Verification. Based on the results of the research and discussion it was concluded that the implementation of the Teacher Competency Test (UKG) policy at Palembang State High School 10 was concluded that in terms of two dimensions, namely the contents of the policy and the context of its implementation. The content of the policy reviewed by the Teacher Competency Test (UKG) is beneficial for teachers and is useful for decision makers to map teacher performance. But in reality, the resources involved in UKG policies are still not optimal, this is evident from the many obstacles that occur in the field. Judging from the context of implementation, the Teacher Competency Test (UKG) policy at Palembang State Senior High School still has a weakness, namely the lack of socialization, which has led to a reaction of rejection from the teacher, and the implementation of training that has not yet run, but one activity towards improving can already be done.